Pengaruh Pendidikan Kesehatan Reproduksi Terhadap Sikap dan Perilaku Seksual Remaja - Amanda Putri Aprilia M.K; Tutik Rahayu; Sri Wahyuni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Reproductive health education for adolescents to prevent risky sexual behavior that has a negative impact on physical and mental health. Adolescence is full of changes that make them vulnerable to misinformation about sexuality. In Indonesia, although reproductive health cases are high, education based on scientific knowledge is still lacking. Therefore, comprehensive education is needed through attractive counseling methods such as animated videos and questionnaires to measure adolescents' understanding. This study used a quantitative research approach. The research design used in this study was a pre-test and post-test approach. Data collection was done in a questionnaire. The number of respondents was 85 with purposive sampling technique. The data obtained was processed statistically using the slovin formula. Based on the results of the analysis, it was found that of the 85 respondents, most had age characteristics of adolescents aged 16-19 years as much as 100%. Gender characteristics in this study were male as many as (42.3%) respondents and female as many as (57.6%) respondents, with the characteristics of most of the highest data being in class XII-1 (35.2%) and the lowest data was class X-1 (30.5%). The results also showed the effect of good attitude before education (88.2%) and (97.6%) good attitude after education and good behavior before education (88.2%), (97.6%) good behavior after education. There is an effect of reproductive health education with attitudes and sexual behavior of adolescents (p value <0.05)